Social work and social welfare : an introduction - Ambrosino, Rosalie; Ambrosino, Robert; Heffernan, Joseph; Shuttlesworth, Guy. ([S.l.] : Brooks Cole, 2012)
This popular text is designed to give you a broad understanding about the social work profession and the role that the profession plays in the social welfare system. The authors demonstrate that there are many reasons why social problems occur. You'll explore the history, values, economic, political and cultural factors that surround these issues, as well as the attempts to solve or address them. Throughout this thought-provoking text, you'll be challenged to think critically about issues in a new way, and gain a more in-depth comprehension and appreciation for this important profession.
Keywords: Public welfare; Social service; United States